A rangewide herbarium‐derived dataset indicates high levels of gene flow in black cherry (Prunus serotina). Issue 3 (8th January 2019) - Konrade, Lauren; Shaw, Joey; Beck, James
Abstract: Isolation by Distance (IBD) is a genetic pattern in which populations geographically closer to one another are more genetically similar to each other than populations which are farther apart. Black cherry ( Prunus serotina Ehrh.) (Rosaceae) is a forest tree species widespread in eastern North America, and found sporadically in the southwestern United States, Mexico, and Guatemala. IBD has been studied in relatively few North American plant taxa, and no study has rigorously sampled across the range of such a widespread species. In this study, IBD and overall genetic structure were assessed in eastern black cherry ( P. serotina Ehrh. var. serotina ), the widespread variety of eastern North America. Eastern North America. Prunus serotina Ehrh. var. serotina (Rosaceae). Dense sampling across the entire range of eastern black cherry was made possible by genotyping 15 microsatellite loci in 439 herbarium samples from all portions of the range. Mantel tests and STRUCTURE analyses were performed to evaluate the hypothesis of IBD and genetic structure. Mantel tests demonstrated significant but weak IBD, while STRUCTURE analyses revealed no clear geographic pattern of genetic groups. The modest geographic/genetic structure across the eastern black cherry range suggests widespread gene flow in this taxon. This is consistent with P. serotina 's status as a disturbance‐associated species. Further studies should similarly evaluate IBD in species characteristic of low‐disturbance forests. Abstract : Isolation by distance (IBD) has been rigorously studied in relatively few widespread North American plant taxa. Our research on gene flow in eastern black cherry trees revealed very weak but significant IBD in this wide‐ranging taxon—a result consistent with black cherry's life history strategies.